Factors That Influence Public Intention To Install Home Charging : The Perspective Of Public Who See And Know About The Electrifyinglifestyle Campaign Electric Vehicle Through Social Media - Febriana, Danny; Taufik Hidayah, Riski (Publisher Cv. Inara, 2025)
Electricity is a fundamental necessity in modern life, and the transition toward the use of environmentally friendly energy has become a global priority to achieve Net Zero Emissions (NZE). The Indonesian government has targeted NZE by 2060, with PLN as the primary actor in supporting energy transition programs such as Electrifying Lifestyle and the development of electric vehicle infrastructure. One significant finding from the Electrifying Lifestyle campaign related to electric vehicles is the remarkable surge in home charging adoption, which recorded a 335% increase in the first semester of 2024 compared to the same period in the previous year. This study aims to analyze the factors influencing public intention to install home charging, particularly through the perspective of the Electrifying Lifestyle campaign on social media. Using the Theory of Planned Behavior, this research explores the influence of variables such as product knowledge, environmental concern, ecological lifestyle, perceived benefits, innovation, and optimism on consumer attitudes, as well as the role of digital campaign effectiveness on brand awareness and purchase intention. The research findings show that respondents' answers for each variable—including consumer attitude, social media marketing, brand awareness, and purchase intention—fall into the good category. Consumer attitude is significantly influenced by product knowledge, environmental concern, ecological lifestyle, perceived benefits, technological innovativeness, and technological optimism. Consumer attitude also has a significant positive effect on purchase intention but is negatively moderated by perceived consumer effectiveness. Additionally, social media marketing has a significant positive effect on both brand awareness and purchase intention, and brand awareness also significantly influences purchase intention. These findings emphasize the importance of digital marketing strategies and strengthening the perceived benefits of technology in promoting the adoption of home charging to support increased environmentally friendly electricity consumption and accelerate the achievement of NZE targets in Indonesia.